joom | júm, n. (Oxford English Dictionary, 2023)
OBJECTIVES: To evaluate the usefulness of transperineal ultrasonography (TPUS) for assessing the activity of perianal fistulas by exploring features associated with the magnetic resonance novel index for fistula imaging in Crohn's disease (MAGNIFI-CD). METHODS: This single-center retrospective study included pediatric patients (age <19 years) who were admitted for an initial evaluation for known or suspected Crohn's disease (CD) and underwent both pelvic MRI and TPUS between September 2021 and October 2023. Patients without perianal fistula or with an interval between pelvic MRI and TPUS >1 week were excluded. Following US features were evaluated: location, longitudinal length of the fistula, extension, diameter perpendicular to longitudinal axis, branching, vascularity, abscess, dominant feature, and proctitis. Multivariable linear regression analysis was performed to identify US features associated with MAGNIFI-CD score. Changes in TPUS features were compared between responder and non-responder groups. RESULTS: A total of 44 patients were included (median age [interquartile range], 14 [13-16] years, boys:girls, 36:8). Multivariable linear regression analysis showed that fistula length (regression coefficient [standard error], 1.48 [0.48]; p = .004) and vascularity (regression coefficient [standard error], 2.87 [1.00]; p = .007) on TPUS were associated with MAGNIFI-CD score. In 25 patients with clinical follow-up data, the extent of change in vascularity was significantly higher in the clinical responder group (change in vascularity treated as an ordinal variable, 0.94 ± 0.77 versus 0.11 ± 0.78; p = .02). CONCLUSION: TPUS, especially through measurement of fistula length and vascularity, is a feasible adjunct to pelvic MRI for evaluating the severity and monitoring the treatment response of perianal fistulas in pediatric patients with CD.